Lingual tonsil lymphatic tissue regrowth in patients undergoing transoral robotic surgery. (24th December 2018) - Iannella, Giannicola; Magliulo, Giuseppe; Montevecchi, Filippo; De Vito, Andrea; Polimeni, Antonella; De Vincentiis, Marco; Meccariello, Giuseppe; D'Agostino, Giovanni; Gobbi, Riccardo; Cammaroto, Giovanni; Stomeo, Francesco; Pang, Kenny P.; et al.
Abstract : Objectives/Hypothesis: To evaluate a possible regrowth of lingual tonsil lymphatic tissue in patients submitted to lingual tonsil resection with transoral robotic surgery (TORS). Study Design: Retrospective Study. Methods: Medical records of patients surgically treated by means of TORS to remove excessive lymphatic tissue of the lingual tonsil were retrospectively reviewed. Postoperative endoscopic data after long‐term follow‐up were analyzed to investigate possible lymphatic tissue regrowth. Preoperative and postoperative lingual tonsil lymphatic tissue were classified according to the standardized Friedman's grading scale ranging from 0 to 4. Results: Sixty‐eight patients (41 male and 27 female; mean age = 51.3 years) were considered suitable for the study analysis. Clinical regrowth was observed in six (8.8%) patients: four (5.9%) and two (2.9%) patients with grade 2 and 3 lymphatic hypertrophy, respectively. No correlation between the grade of regrowth, the time interval from surgery, and the volume of lymphatic tissue removed was found. Conclusions: The lymphatic tissue regrowth after TORS resection appears to be very low. Level of Evidence: 4 Laryngoscope, 129:2652–2657, 2019